OP0228 GSK3196165 AN INVESTIGATIONAL ANTI-GM-CSF MONOCLONAL ANTIBODY, IMPROVES PATIENT REPORTED OUTCOMES IN A PHASE IIB STUDY OF PATIENTS WITH RHEUMATOID ARTHRITIS (RA). (June 2019) - Buckley, Chris; Campos, Jesus Simon; Zhdan, Vyacheslav; Becker, Brandon; Chauhan, Deven; Davy, Katherine; Hawkes, Carol; Inman, David; Layton, Mark; Patel, Jatin; Saurigny, Didier; Mitchell, Nina; et al.
Abstract : Background: GSK3196165 is a human mAb that inhibits GM-CSF, a key driver in a broad range of immune-mediated conditions (Hamilton, 2016). In trials of patients with RA, inhibition of GM-CSF signaling has resulted in clinical benefit. GM-CSF is not only a key mediator of inflammation, but emerging science suggests it is also an important regulator of pain. Objectives: To evaluate the treatment effect of GSK3196165 on pain, fatigue, physical functioning, mental functioning and global assessment of disease, in patients with moderate-to-severely active RA. Methods: 222 adult patients with active, moderate-severe RA (ACR 2010 criteria), ≥4 each of swollen and tender joints, DAS28(CRP) ≥3.2 and CRP ≥5.0 mg/L, were randomized equally to placebo or GSK3196165 22.5mg, 45mg, 90mg, 135mg or 180mg SC weekly for 5 injections, then every other week until Week 50. The Patient Reported Outcomes (PROs) measured throughout the study included, pain Visual Analogue Scale (VAS), Patient's Global Assessment of Arthritis (PtGA), Health Assessment Questionnaire - Disability Index (HAQ-DI), Brief Fatigue Inventory (BFI) Question 3, the Functional Assessment of Chronic Illness Therapy – Fatigue (FACIT-F), and the 36-item short form health survey (SF-36). The primary outcome was the proportion of patients who achieved remission (DAS28(CRP) <2.6) at Week 24 and the data has been previously reported (Buckley, 2018). Results: 37 patients were randomised to each treatment group. The observed GSK3196165 pharmacokinetic exposures were lower than anticipated but despite this, there was a rapid and substantial improvement in RA symptoms in patients treated with GSK3196165 compared with placebo. The table below summarizes the change from baseline data for the GSK3196165 180 mg dose and placebo at Week 12. An increase in the FACIT-F and SF-36 scores and a decrease in all other scores indicate an improvement in RA symptoms. Conclusion: The results of this Phase IIb study showed that GSK3196165 substantially improved the scores of a range of PRO measures among RA patients. In particular, there was a highly significant improvement in pain; a key symptom of RA. These effects were observed despite achieving much lower drug exposure than predicted. Further studies are required to confirm the additional patient relevant benefits that are expected to arise from increased exposure to GSK3196165. References: [1] Hamilton JA, Cook AD, Tak PP. Anti-colony-stimulating factor therapies for inflammatory and autoimmune diseases. Nat Rev Drug Discov 2016; 16:53-70 [2] Buckley C, et al. A Phase IIb Dose-Ranging Study of Anti-GM-CSF with Methotrexate Treatment in Patients with Rheumatoid Arthritis (RA) and an Inadequate Response to Methotrexate. Arthritis Rheumatol. 2018;70 (Suppl 10): abs 1938 Disclosure of Interests: Chris Buckley Consultant for: GlaxoSmithKline, Jesus Simon Campos: None declared, Vyacheslav Zhdan: None declared, Brandon Becker Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, Deven Chauhan Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, Katherine Davy Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, Carol Hawkes Shareholder of: I own shares in GlaxoSmithKline, Employee of: I am currently an employee of GlaxoSmithKline, David Inman Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, Mark Layton Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, Jatin Patel Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, Didier Saurigny Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, Nina Mitchell Shareholder of: GlaxoSmithKline, Employee of: Former GlaxoSmithKline employee, Russell Williamson Shareholder of: GlaxoSmithKline, Employee of: Former GlaxoSmithKline employee, Paul Peter Tak Shareholder of: GlaxoSmithKline, Employee of: Former GlaxoSmithKline employee